Enforceability of Digital Contracts in the Era of E-Commerce: Legal Perspectives and Challenges - Heni Satar Nurhaida (Faculty of Law, Universitas Pekalongan, 2024)
The rapid evolution of digital technology has revolutionized global commercial interactions, positioning e-commerce as a cornerstone of international trade. Digital contracts facilitate online agreements but face significant legal and regulatory challenges concerning their enforceability across different jurisdictions. This article explores the legal perspectives affecting the recognition and enforcement of digital contracts, focusing on the validity of electronic signatures, jurisdictional complexities, consumer protection, and data privacy compliance. Employing a qualitative, doctrinal legal research approach, this study reviews key regulations such as the E-SIGN Act, UETA, eIDAS, and GDPR, alongside relevant international conventions. Findings reveal that while strides have been made toward harmonizing digital legal frameworks, disparities among jurisdictions, consumer rights safeguards, and stringent data privacy laws present substantial obstacles. The study underscores the need for policy improvements and greater international cooperation to establish a more consistent and secure legal environment for cross-border digital contracts.